The epigraphy and history of Boeotia : new finds, new prospects - Papazarkadas, Nikolaos, 1974- (Brill Studies in Greek and Roman Epigraphy, 2014)
Over the past 20 years, Boeotia has been the focus of intensive archaeological investigation that has resulted in some extraordinary epigraphical finds. The most spectacular discoveries are presented for the first time in this volume: dozens of inscribed sherds from the Theban shrine of Heracles; Archaic temple accounts; numerous Classical, Hellenistic and Roman epitaphs; a Plataean casualty list; a dedication by the legendary king Croesus. Other essays revisit older epigraphical finds from Aulis, Chaironeia, Lebadeia, Thisbe, and Megara, radically reassessing their chronology and political and legal implications. The integration of old and new evidence allows for a thorough reconsideration of wider historical questions, such as ethnic identities, and the emergence, rise, dissolution, and resuscitation of the famous Boeotian koinon . Contributors include: Vassilios Aravantinos, Hans Beck, Margherita Bonanno, Claire Grenet, Yannis Kalliontzis, Denis Knoepfler, Angelos P. Matthaiou, Emily Mackil, Christel Müller, Nikolaos Papazarkadas, Isabelle Pernin, Robert Pitt, Adrian Robu, and Albert Schachter.